Putting Creativity to Work: The Implementation of Creative Ideas in Organizations - Baer, Markus (Academy of Management Journal, 2012)
Tbe production of creative ideas does not necessarily imply their implementation. This study examines tbe possibility tbat tbe relation between creativity and implementation is regulated by individuals ' motivation to put tbeir ideas into practice and their ability to network, or, alternatively, tbe number of strong relationsbips they maintain. Using data from 216 employees and tbeir supervisors, results indicated tbat individuals were able to improve the otberwise negative odds of their creative ideas being realized wben they expected positive outcomes to be associated with tbeir implementation efforts and wben tbey were skilled networkers or bad developed a set of strong "buy-in" relationsbips. "Ideas are useless unless used " (Levitt, 1963: 79). Although few would dispute the validity of this statement, studies that directly examine the condi-tions that determine when creative ideas are con-verted into actual innovations, that is, imple-mented or used, are relatively rare. This lack of systematic attention is especially surprising given that innovation, particularly in dynamic contexts, is widely recognized as being critical to the growth and competitiveness of organizations (e.g.. Roth & Sneader, 2006; Tellis, Prabhu, & Chandy, 2009) and, as a consequence, has been of longstanding interest to scholars and practitioners alike (e.g.,